(untitled) (Studia Doctoralia Psychology and Educational Science, 2025)
between emotional instability and loneliness, and to test the moderating role of social support and social media use on the relationship between neuroticism and loneliness. The sample consisted of 152 individuals (n = 110, 72.4% women and n = 42, 27.6% men, SD =11.87). Demographic data were collected, along with data regarding levels of neuroticism, loneliness, perceived social support and social media use. Only one hypothesis, the one concerning the relationship between neuroticism and loneliness was supported, while the rest of the hypotheses were rejected. Results suggest that although neurotic individuals benefit from social support, it does not have a perceived effect on the loneliness they experience. Moreover, despite the fact that neurotics often engagge in social comparison when using social media, this does not influence the level of loneliness they feel. Limitations and future research directions are outlined later on in the study.